(3TQM GdETGQGJ hGdJfHjgGJs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3eMeO MSjf Hf HgGOQ s)
(3ChdgG (B:s
(3hHYO ceG Cf Cced GdeYGQa hCLdgG TCfkG s
(3BNQgG (B:s
(3hCeG CJhbY eef jbY Edjg cJGHi gPG Cf jUdM eG jYJHQ Ydjg ef GdNdd s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs